Shaking table model test on Shanghai World Financial Center Tower. - Lu, Xilin (Earthquake engineering & structural dynamics.)
The height of 101-storey Shanghai World Financial Center Tower is 492m above ground making it possible the tallest building in the world when completed. Three parallel structural systems including mega-frame structure, reinforced concrete and braced steel services core and outrigger trusses, are combined to resist vertical and lateral loads. The building could be classified as a vertically irregular structure due to a number of stiffened and transfer stories in the building. Complexities related to structural system layout are mainly exhibited in the design of services core, mega-diagonals and outrigger trusses. According to Chinese Code, the height 190 m of the building clearly exceeds the stipulated maximum height of for a composite frame/reinforced concrete core building. The aspect ratio of height to width also exceeds the stipulated limit of 7 for seismic design intensity 7. A 1/50 scaled model is made and tested on shaking table under a series of one and two-dimensional base excitations with gradually increasing acceleration amplitudes. This paper presents the dynamic characteristics, the seismic responses and the failure mechanism of the structure. The test results demonstrate that the structural system is a good solution to withstand earthquakes. The inter-storey drift and the overall behaviour meet the requirements of Chinese Design Code. Furthermore, weak positions under seldom-occurred earthquakes of seismic design intensity 8 are found based on the visible damages on the testing model, and some corresponding suggestions are proposed for the engineering design of the structure under extremely strong earthquake.